Adenocarcinoma of Left Maxilla: Case Report (Clinico Radiologic, Pathologic Features and Management) (Global Journal of Medical Research, 2018)
Very rarely malignant tumors of the nasal cavities and paranasal sinuses are seen. The incidence is less than one per cent of all tumors and less than three per cent of head and neck tumors in which most common is the carcinoma of the maxillary sinus. In this a case of adenocarcinoma with histopathology and treatment planning is discussed.